Strategi Pengembangan Ekowisata Berbasis Masyarakat di Desa Wisata Tipang Kecamatan Baktiraja Kabupaten Humbang Hasundutan Tahun 2023 - Sari Lastarida Nainggolan; Maringan Sinambela; Masniar. H. Sitorus; Wilmar E Simandjorang; Bambang T J Hutagalung (Lembaga Pengembangan Kinerja Dosen, 2023)
Research objectives To find out strategies that can be implemented in developing community-based Ecotourism in Tipang village, Baktiraja District, Humbang Hasundutan Regency in 2023. To find out what factors support and inhibit the development of community-based Ecotourism in Tipang tourist village. Using a qualitative research method with a descriptive approach through in-depth interview techniques with informants. From the results of research conducted by researchers, the Tipang Tourism Village, Baktiraja District, Humbang Hasundutan Regency is still in the pioneering stage. Therefore, for the Tipang Tourism Village development strategy there are stages that must be carried out, especially the process of approaching the community and providing guidance to assist the community's human resources. As well as the existence of supporting and inhibiting factors in the community-based ecotourism development strategy, more attention must be paid by utilizing the potential of the Tipang Tourism Village. The strategies that have been implemented in the tourism community are: 1. Becoming a government partner in encouraging and disseminating tourism awareness among the community. 2. Providing participation in various related training, such as understanding what tourism potential is and also what it is like to develop a tourist village. 3. Mapping tourism potential, where Pokdarwis has data from every tourist location point in Tipang Tourism Village. 4. Create a tour package where this tour package has a tariff according to the tourist's trip in the Tourism Village and what the tourist's activities will be in the future. 5. Promoting tourism products carried out by Pokdarwis so that Tipang Tourism Village becomes increasingly well known and penetrates the outside world. Potential villages with culture and daily traditions of the community that can be developed as tourist village attractions. Through the factors that influence the development of this tourist village, there are attractions, amenities, accessibility and also superior human resources.